MP12: Preparing emergency patients and providers study: patient expectations and factors leading to presentation. (May 2019) - Rose-Davis, B.; Cassidy, C.; MacPhee, S.; Chiasson, D.; Nunn, J.; Curran, J.
Abstract : Introduction : Effective communication to develop a shared understanding of patient expectations is critical to a positive encounter in the Emergency Department (ED). However, there is limited research examining Patient/Caregiver (P/C ) expectations in the ED and what factors lead to P/C presentation. This study aims to address this gap by answering the following questions: 1) What are common P/C reported factors affecting ED presentation? 2) What are common P/C expectations of an ED visit? 3) How do P/C expectations vary based on ED site or factors affecting presentation in the ED?Methods : The Preparing Emergency Patients and Providers (PrEPP) tool was designed to collect P/C expectations, worries, perceived causes of symptoms, and factors affecting presentation from a convenience sample of patient visits to the emergency department (ED). The PrEPP tool was provided to all P/Cs with CTAS 2-5 when they registered at one of 4 EDs in the Halifax area from January to June 2016. Completed tools were collected in a REDCap database where qualitative data was coded into categories (i.e. presenting illness, injury). Descriptive and chi-squared statistical analyses were performed.Results : In total, 11, 418 PrEPP tools were collected; representing 12% of the total ED visits to the 4 ED sites during the study period. The main factors affecting ED presentation were: self-referral 68%, family/friends 20%, telehealth 8%, unable to see their GP 7%, GP referral 6%, or walk-in-clinic 5%. P/Cs main causes of worry were: presenting illness 19%, injury 15%, or pain 14%. The main expectations for the ED visit were to get a: physician's opinion 73%, x-ray 40%, or blood test 20%. Most P/Cs indicated they did not expect medication during (63%), or after (66%), their ED visit. There were significant differences in P/C expectations between adult and pediatric EDs (χ2 = 720.949, df = 14, P = 0.000) and those P/Cs unable or able to access primary care prior to ED presentation (χ2 = 38.980, df = 1, P = 0.000). The rate of expecting a physician's opinion at the pediatric ED was higher than the adult ED (77.6% vs 70.9%), while lower for expecting CT/MRIs (4.6% vs 11.4%). P/Cs who were unable to access primary care prior to ED presentation expected services which were available at primary care at a higher rate than those who accessed primary care (58.5% vs 36.7%).Conclusion : Our findings identify some of the factors that influence P/C's decision to present to the ED and their expectations of the ED visit.